The impact of the European Court of Justice on neighbouring countries - Reich, Arie; Micklitz, Hans-W. (Oxford : Oxford University Press, 2020)
Exploring the external impact of the Court of Justice of the European Union, this text delves into the influence its judgments have outside EU borders and particularly on the legal systems of countries in the European neighbourhood. A team of scholars from non-EU countries provided analysis and insight into this project.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 14, 2020).
Keywords: Court of Justice of the European Union -- Influence; Law -- International unification